MENDORONG PENERAPAN BASIS AKRUAL DALAM PENGELOLAAN KEUANGAN DESA (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
The village government, as the manager and organizer of the policy, must be able to carry out village financial management in a reliable, effective, efficient, and accountable manner. Prior to the issuance of a government regulation governing a regional financial accounting system that used an accrual basis, the village government financial management system still used a cash-based, single-entry accounting system. Furthermore, in its development, it uses a cash basis for accruals (hybrid). Efforts to apply the accrual basis in village financial governance intend to improve the quality of village financial reports. Financial reports become more accurate so that they can be used as a tool to measure the performance of village government. Another benefit of the accrual basis is its ability to show how the village government fulfills its funding needs, finances all development activities, and evaluates the village's financial ability to finance and fulfill its obligations. Seeing the benefits, it is time for village financial management to fully use the accrual basis. The village government will be more accountable, transparent, responsible, and have projection capabilities when preparing village development plans.